2016
DOI: 10.1111/bjop.12181
|View full text |Cite
|
Sign up to set email alerts
|

Country roads, take me home… to my friends: How intelligence, population density, and friendship affect modern happiness

Abstract: We propose the savanna theory of happiness, which suggests that it is not only the current consequences of a given situation but also its ancestral consequences that affect individuals' life satisfaction and explains why such influences of ancestral consequences might interact with intelligence. We choose two varied factors that characterize basic differences between ancestral and modern life - population density and frequency of socialization with friends - as empirical test cases. As predicted by the theory,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
43
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 88 publications
3
43
1
Order By: Relevance
“…This contrasts with, for example, the results of Ballas and Tranmer (2012), who found no statistically significant geographical variations in happiness. However, it seems that the density of the immediate surroundings does not have a relationship between well-being in any of the specifications, which contrasts with the result of Li and Kanazawa (2016) on the negative relationship between census-block group density and global life satisfaction. Thus, the results suggest that densifying infill construction does not necessarily lead to lower SWB, at least not in the long run, even if the disturbances related to the construction phase can probably be accompanied with short-term fluctuations and discontent.…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…This contrasts with, for example, the results of Ballas and Tranmer (2012), who found no statistically significant geographical variations in happiness. However, it seems that the density of the immediate surroundings does not have a relationship between well-being in any of the specifications, which contrasts with the result of Li and Kanazawa (2016) on the negative relationship between census-block group density and global life satisfaction. Thus, the results suggest that densifying infill construction does not necessarily lead to lower SWB, at least not in the long run, even if the disturbances related to the construction phase can probably be accompanied with short-term fluctuations and discontent.…”
Section: Discussioncontrasting
confidence: 74%
“…Likewise, Ferreira et al (2013) found no significant relation with life satisfaction and density. However, Li and Kanazawa (2016) found population density at the level of the census block group to decrease self-reported life satisfaction, and a similar finding was made by Cramer, Torgersen, and Kringlen (2004). Similarly, Schwanen and Wang (2014) suggest that there is an inverse relationship between overall life satisfaction and level of urbanization at the intra-urban scale in Hong Kong, China.…”
Section: Spatial Factors Explaining Subjective Well-beingsupporting
confidence: 57%
See 1 more Smart Citation
“…A related study found that individuals with Machiavellian traits both rated friendships as less important and tended to form low-quality friendships (Lyons & Aitken, 2010). Socially skilled and pro-social children form more and longer lasting friendships than aggressive and manipulative children do (Parker & Seal, 1996), while highly intelligent individuals appear to have fewer friends and to find it more difficult or less rewarding to interact with friends compared to individuals with normal levels of intelligence (Janos, Marwood & Robinson, 1985;Li and Kanazawa 2016). Previous studies have also highlighted how friendship characteristics affect personality, and vice versa.…”
mentioning
confidence: 99%
“…Whilst subjective wellbeing is positively genetically correlated with measures of cognition, we identify a small but statistically significant negative correlation between measures of correlation and the two phenotypes. A recent study highlighted that people with very high IQ scores tend to report lower satisfaction with life with more frequent socialization 44 . This also highlights the distinctions between subjective wellbeing and social relationship satisfaction.…”
Section: Discussionmentioning
confidence: 99%